Upaya Penanaman Nilai Karakter Cinta Tanah Air di Lingkungan Sekolah - Sholawati Nova; Tia Monika; Ratna Sari Dewi (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to examine the strategy of developing the character of love for the country among students through education, using the literature study method. Education is a major factor in building a strong and competitive nation amidst the challenges of the fourth industrial revolution and globalization. The development of the character of patriotism is essential to prepare young people who are committed to national values and have the spirit of nationalism. This literature review explores the concept of patriotism, the role of teachers, and effective learning strategies in the school environment. The results of the analysis show that the development of the character of patriotism can be realized through various holistic educational activities, such as intracurricular, co-curricular, and extracurricular. The active role of teachers in instilling national values and involving students in local cultural activities is also very significant. A supportive school culture and extracurricular activities such as scouting also play an important role in fostering a sense of love for the country. The study concludes that a comprehensive strategy involving all relevant parties, including the government, schools and parents, is needed to overcome challenges and strengthen the character of patriotism in the digital era.